1994
DOI: 10.1002/pc.750150505
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fiber length, fiber orientation, and interfacial adhesion on poly (butylene terephthalate)/polyethylene alloys reinforced with short glass fibers

Abstract: Blends of poly(butylene terephthalate) and high density polyethylene at a ratio of 80:20 wt% were reinforced with short glass fibers varying from 10 to 30 wt% to enhance mechanical properties. Considerable fiber damage occurred during injection molding, reducing the number average fiber length from the starting value of 4.5 mm to < 1 mm. This value decreased with increasing fiber content, which is also responsible for lowering the reinforcement efficiency. The variation in mechanical properties has been explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…At the lowest CF loading of 0.5 wt%, the large majority of the fibers are within the 100-400 lm range with a mean average of 217 lm. By increasing the CF loading to 2wt% the mean length shifts to lower values, which are consistent with the literature [7]. At this concentration the large majority of the fibers (65%) are now being below 200 lm in length and the mean average is 170 lm.…”
Section: Fiber Length Distributionsupporting
confidence: 91%
See 1 more Smart Citation
“…At the lowest CF loading of 0.5 wt%, the large majority of the fibers are within the 100-400 lm range with a mean average of 217 lm. By increasing the CF loading to 2wt% the mean length shifts to lower values, which are consistent with the literature [7]. At this concentration the large majority of the fibers (65%) are now being below 200 lm in length and the mean average is 170 lm.…”
Section: Fiber Length Distributionsupporting
confidence: 91%
“…However, in the particular case of a brittle type of fibrous reinforcement such as glass and carbon fibers, the shear mechanical action of the melt‐compounding process often results in breakage of the fibers, which in turn also limits the micro‐mechanical reinforcing efficiency of the fibers . Numerous studies have reported the relationship between fiber length and mechanical performance of the micro‐composites . It is now well established that in order to effectively improve the strength and modulus of the matrix, the fiber length needs to be preserved as much as possible during the process .…”
Section: Introductionmentioning
confidence: 99%
“…8a, we use polypropylene (E PP = 1.665 GPa, ν PP = 0.36, see [47] and [48]) in the matrix and E-glass (E E = 73 GPa, ν E = 0.18, see [49]) in the fibers and vary the number of voxels to get an impression on the convergence rate of the relative error for increasing resolution. To obtain the geometries at the required resolution we use a voxel-representation of the fiber-reinforced plastic (FRP) with 4096 3 voxels and downsample according to Section 3.3.3.…”
Section: Fiber Reinforced Plastic (Frp)mentioning
confidence: 99%
“…On the other hand, addition of short fibers usually reduces the toughness in ductile matrix composites ( 1 1 -13). There are only a few studies on the effect of fiber content on the fracture toughness of short glass fiber reinforced rubber toughened polymer blends (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%